Effect of agricultural by-product diets on carcass characteristics of four types of cattle in the feedlot - Ismail, Dahlan; Haron, A. Rahman; Sukri, M. H. I. (Asian-Australasian Association of Animal Production Societies, 1992)
Five type of formulated diet from agricultural by-products (ABP) were fed to four breedtype of cattle in feedlot. The ABP used are palm kernel cake (PKC), palm press fibre (PPF), palm oil mill effluent (POME), cocoa pod (COP), coffee pulp (COF) and pineapple waste (PAP). The formulated diets are PS (52% PKC, 15% PPF and 30% POME), PF (57% PKC, 20% PPF and 20% POME), PA (2% PKC and 55% PAP), CO (42% PKC and 55% COP) and CF (67% PKC and 30% COF) with 1% urea, 1% NaCl and 1% vitamins premix. The cattle breedtypes are Kedah-Kelantan (KK), Brahman-KK (BK), Hereford-KK (HK) and Sahiwal-Friesian (SF). The result showed that breedtype significantly affect all the carcass characteristic except dressing percentage. Each breedtype has it`s specific carcass characteristics. HK cattle gave high marbling, BK has high % of carcass bone, KK has high % of carcass meat and low % of carcass fat (lean meat type) and SF has high % of carcass fat. Diet-type significantly affect the deposition of fat in the carcass. High moisture diets (PA and CO) produced significantly higher % carcass bone, the lowest % carcass fat and the highest % carcass meat (65.3%). PF, CF, PA and CO diets produced 63.4%, 59.9%, 55.3% and 54.1% carcass meat respectively.